Find the quotient.(6x 2 + 23x + 20) ÷ (5 + 2x)

3x - 4
3x + 4
3x +19

Answers

Answer 1
Answer: (6x^(2) + 23x + 20)/(2x + 5) = (6x^(2) + 15x + 8x + 20)/(2x + 5) = (3x(2x) + 3x(5) + 4(2x) + 4(5))/(2x + 5) = (3x(2x + 5) + 4(2x + 5))/(2x + 5) = ((3x + 4)(2x + 5))/(2x + 5) = 3x + 4

The answer is B.
Answer 2
Answer:

Answer:

3x+4

Step-by-step explanation:


Related Questions

LOTS OF POINTS, THANKS, AND BEST ANSWER!!The dimensions of a conical funnel are shown below:A conical funnel is shown with the height of the cone as 8 inches and the radius of the base as 3 inches.Nisha closes the nozzle of the funnel and fills it completely with a liquid. She then opens the nozzle. If the liquid drips at the rate of 15 cubic inches per minute, how long will it take for all the liquid to pass through the nozzle? (Use π = 3.14.)
3t<-15 a. t<-5 b. t>-5 c. t<-45 d. t>-45
Can anybody answer this simple math question ive attached please
Linda walked 3/4 of the length of the Tremont Trail before stopping for a rest. How far had Linda walked on the trail? Tremont Trail:3 1/2 miles Seton Trail:1 1/4 miles Wildflower Trail:2 3/8 miles 15 POINTS WILL MARK BRAINLIEST PLZ HURRY
3-3x6+2= -13 ? Is that correct

Will mark brainliest

Answers

2.21 is the answer :-/

A ball is thrown horizontally with a speed of 10 m/s, from the edge of the top of the building of height 19.6m, and later strikes the ground.1) For how long was the ball in the air?
2)what is the vertical component of the velocity just before the ball strikes the ground?
3) what is the horizontal component of the velocity just before the ball strikes the ground?
4)how far from the base of the building did the ball strike the ground?
5) what is the speed of the ball just before it strikes the ground?

Answers

1) You need to solve t - 19.6=.5(9.8)t^2
2) Then solve fvf^2=2(9.8)(19.6)
3) As it's constant it is still 10m/s
4) You need to 
use the time from part 1 times 10m/s
5) Use Pythagorean theorem with 10m/s and vf

I am pretty sure it will help you.

Mrs. Thomas bought 2/4 yard of one fabric and 3/4 yard of a different fabric. How many total yards of fabric did she buy?

Answers

Plzz mark brainlest

Answer:

1   1/4

Step-by-step explanation:

You don't add the bottom one you have to dived it by two and it is a decmail one so you have to add it it and you want to keep the bottom and it is fifteen sone you want to add the one as the whole number and keep the one for the top and keep the bottom one so you will get 1 1/4 and I use this one and it was right!

It is 5/4 yards, you just add 
When the denominator ( the bottom number ) is the same, just add the numerator ( the top number ) together :) 
hope this help

Find the 168th term of arithmetic sequence {a_{n}, n = 1, 2, 3, . . .} with common ifference d = 1.5 and first term a_{1} = 2.

Answers

a_1=2;\ d=1.5\n\na_n=a_1+(n-1)d\n\na_n=2+(n-1)\cdot1.5=2+1.5n-1.5=0.5+1.5n\n\na_(168)=0.5+1.5\cdot168=0.5+252=252.5

Three multiplied by the sum of 4 and a number is the same as 18 more than the number. Find the number.. . If n is \"the number,\" which equation could be used to solve for the number?. . . 3n + 4 = n + 18. 4(3 + n) =n + 18. 3(4 + n) =n + 18. 3(4 + n) + 18 > n

Answers

Answer:

3(n+4)=n+18

The value of n is 3

Step-by-step explanation:

Let n be the required number.

Sum of 4 and the number n is (n +4)

Three multiplied by the sum of 4 and the number= 3(n +4)

Now, 18 more than the number = (n + 18)

From, the given directions, we can write the equation

3(n+4)=n+18

Now, we solve this equation for n

Distribute 3 over the parenthesis

3n+12=n+18

Subtract n to both sides

2n+12=18

Subtract 12 to both sides

2n=6

Divide both sides by 2

n=3

Therefore, the required equation is

3(n+4)=n+18

The value of n is 3

Translate the statement to algebraic language:1) Call x the unknown number2) The sum of 4 and a number = 4 + x3) Three multiplied by the sum of 4 and a number = 3(4 + x)4) Is the same as 18 more than the number: 3( 4 + x) = 18 + xSolve the equation:3*4 + 3x = 18 + x3x - x = 18 - 122x = 6x = 6/3x = 2.The number is 2.

Write x^2 − 8x + 13 = 0 in the form (x − a)^2 = b, where a and b are integers.(x − 4)^2 = 3
(x − 3)^2 = 2
(x − 2)^2 = 1
(x − 1)^2 = 4

Can anyone show the steps on how to get the answer?

Answers

Sure.
The answer is (x-4)^2 = 3

Procedure

Complete a perfect square trinomial to factor:

x^2 - 8x + 13 = 0

Notice that -8x = 2(x)(4)

Given tha x is the square root of x^2, we want to include the square of 4, which is 16.

We must just add 16 to the first two terms, which, of course, obliges to substract the same number to maintain the equality. This way:

(x^2 - 8x + 16) + -16 + 13= 0

Now the three terms in parenthesis can be factor as a binomial squared:

(x - 4)^2 + 13 -16 =0

(x - 4)^2 - 3 = 0

(x - 4)^2 = 3 Which is the answer.

Let me know whether you could follow the explanation.